The determinants of Malaysia’s exchange rate / Fify Farahana Mohd Azmy - Mohd Azmy, Fify Farahana (Faculty of Business and Management, 2018)
The study examines the relationships that between exchange rate (ER) and the determinants inflation rate (INF), gross domestic product (GDP), interest rate (IR), import (IMP) and export (EXP) in the recent years in Malaysia over the period of 1987- 2015 which contains yearly data. The data collected from World Development Indicator. After examined the time series characteristics of the data with Augmented Dickey-Fuller (ADF) unit roots test of stationarity and Philipp Perron (PP) test, this paper applies Autoregressive Distributed Lag Model (ARDL) as main method in order to define the statistical relationship among the variables. In Diagnostic Checking, some tests done to check the significant presents of autocorrelation, heteroscedasticity, the normality of data distribution and model specification. The result of this study show that there is significant for long run relationship between exchange rate and three explanatory variables which are gross domestic product, inflation rate and export while interest rate and import did not have any relationship with the ER.